2021
DOI: 10.1161/circulationaha.121.053678
|View full text |Cite
|
Sign up to set email alerts
|

Health Impact and Cost-Effectiveness of Achieving the National Salt and Sugar Reduction Initiative Voluntary Sugar Reduction Targets in the United States: A Microsimulation Study

Abstract: Background: High intake of added sugar is linked to weight gain and cardiometabolic risk. In 2018, the US National Salt and Sugar Reduction Initiative (NSSRI) proposed government supported voluntary national sugar reduction targets. This intervention's potential health and equity impacts, and cost-effectiveness are unclear. Methods: A validated microsimulation model, CVD-PREDICT, coded in C++, was used to estimate incremental changes in type 2 diabetes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…We have not performed either supply chain or economic modeling to demonstrate the cost effectiveness or environmental sustainability of this approach at an industrial level. Also, while we ( 114 ) and others ( 115 ) have previously performed microsimulation analyses to demonstrate the health and healthcare benefits of sugar reduction, a similar analysis on ultraprocessed foods has not yet been done. Lastly, we believe that employing the Metabolic Matrix will save governments healthcare costs resulting from the premature development of NCD’s.…”
Section: Discussionmentioning
confidence: 99%
“…We have not performed either supply chain or economic modeling to demonstrate the cost effectiveness or environmental sustainability of this approach at an industrial level. Also, while we ( 114 ) and others ( 115 ) have previously performed microsimulation analyses to demonstrate the health and healthcare benefits of sugar reduction, a similar analysis on ultraprocessed foods has not yet been done. Lastly, we believe that employing the Metabolic Matrix will save governments healthcare costs resulting from the premature development of NCD’s.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the US National Salt and Sugar Reduction Initiative [ 67 ] is meant to encourage food companies to reformulate products voluntarily in line with set standards and could address nutrition security directly by altering the quality of accessible foods. A microsimulation study has suggested that achieving such reformulation goals could lead to reductions in CVD events and mortality and increases in quality-adjusted life-years, even with imperfect compliance [ 68 ].…”
Section: Federal State and Local Policies And Programsmentioning
confidence: 99%
“…Given that income and food insecurity are associated with the quality of food consumed away from home, instead of restricting access to an important food source, future work could explore how to improve the quality of low-cost restaurant meals and convenience foods by implementing national sodium and sugar reduction initiatives. 36 Nutrition practitioners and researchers could also partner with restaurants to make balanced choices more accessible by providing healthier side dishes, replacing sugarsweetened beverages, and serving appropriately sized meals on children's menus.…”
Section: Implications For Research and Practicementioning
confidence: 99%